Type of Collaborative Learning of Kagan Framework in Microteaching Course of ELESP UNJ - Rafiqa Tanzilla; Ellis Tamela (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2021)
This study aims to identify what collaborative learning is in the microteaching class of the English Language Education Study Program, Jakarta State University. Indicators in collaborative learning are based on research and statements from Kagan (2015). In conducting this research, data were collected from the student-student teacher activities and interactions in microteaching class activities. The finding showed that type of collaborative learning in this course belonged to learning together. The activities in learning together were when the student teacher decided on group size, assign students to groups, arrange the room, assign roles, explain the academic task, monitor student's behavior, provide task assistance, and provide closure. The results of the study hopefully can give insights on how to conduct collaborative learning an any subjects or courses.